2013
DOI: 10.1088/0960-1317/23/2/025014
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined cryogenic cooler for cooling electronic devices down to 30 K

Abstract: Cryogenic temperatures are required for improving the performance of electronic devices and for operating superconducting sensors and circuits. The broad implementation of cooling these devices has long been constrained by the availability of reliable and low cost cryocoolers. After the successful development of single-stage micromachined coolers able to cool to 100 K, we now present a micromachined two-stage microcooler that cools down to 30 K from an ambient temperature of 295 K. The first stage of the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Still, the few groups that have been pursuing this have made good demonstration of the potential in working at high pressures. [6][7][8][9][10] In inertial focusing, it is generally accepted that in a straight channel, the migration and equilibrium of particles are mainly due to two forces; the shear gradient lift force, directed towards the walls of the channel and originated from the non-zero curvature of the flow profile, and the wall force, repelling particles from the walls and originated from the interaction of the stresslet around the particle and the wall. Reviews on the phenomenon can be found elsewhere, [11][12][13][14] but an introduction with key points is included in the following paragraphs to ease the understanding of the results and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the few groups that have been pursuing this have made good demonstration of the potential in working at high pressures. [6][7][8][9][10] In inertial focusing, it is generally accepted that in a straight channel, the migration and equilibrium of particles are mainly due to two forces; the shear gradient lift force, directed towards the walls of the channel and originated from the non-zero curvature of the flow profile, and the wall force, repelling particles from the walls and originated from the interaction of the stresslet around the particle and the wall. Reviews on the phenomenon can be found elsewhere, [11][12][13][14] but an introduction with key points is included in the following paragraphs to ease the understanding of the results and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The application potential of the microcooler coupled with electronic devices has been demonstrated by cooling an yttrium barium copper oxide film through its superconducting phase transition by using a 30 K two-stage microcooler [19]. This work demonstrates the application potential of the microcooler for integration with electronic devices, such as infrared detectors, LNAs and superconducting sensors.…”
Section: Utilization Of Microcoolers For Cooling Electronicsmentioning
confidence: 81%
“…In order to increase the heat transfer between pre-cooler and the first evaporator, they are integrated into a compact design with a relatively large heat-transfer area. Here, the low-pressure fluid of the first stage, after expansion, absorbs heat from the high-pressure fluid of the second stage [19]. Similar to the single-stage microcooler development, the two-stage microcooler (as shown in figure 2b) was fabricated using micromachining technology only.…”
Section: Two-stage Coolermentioning
confidence: 99%
“…In Little's work [3], [4], [12], and [13], high gross refrigeration powers were reached by using relative high pressure ratio nitrogen (16.5:0.1 MPa) and flow-rate (107 μmol/s). In University of Twente's work [14] and [15], a low emissivity metal thin film was coated on the heat exchanger to reduce its radiation loss, however, a much higher pressure (8 MPa) and flow-rate were used in order to compensate the loss. Clearly the thermal isolation is extremely important for such a small size micro cryogenic cooler with limited gross refrigeration (30.3 mW gross refrigeration at 10 sccm flow rate using equation 1).…”
Section: Thermal Isolation Of MCCmentioning
confidence: 99%